Ten years of Novo Basquete Brasil: a descriptive analysis about its participating teams and the competitive balance of the league - Clara Modeneis Dalla Costa Ziani; Leonardo Risso Cavalini; Larissa Rafaela Galatti; Leandro Carlos Mazzei (Federación Extremeña de Balonmano; University of Extremadura, 2019)
Abstract Considering that the Novo Basquete Brasil (NBB), organized by the Liga Nacional de Basquete (LNB), is the main national basketball competition in Brazil, the objectives of this work are to present the diagnoses on the participation of the teams and the competitive balance in those 10 years of the NBB. A total of 32 teams have been identified that have participated at least once in the competition. It was identified that none were from the North region, 02 (6%) from the Northeast region, 02 (6%) from the Midwest region, 06 (19%) from the South region and 22 (69%) from the Southeast region. 10 (31%) are traditional multi-sport club teams from the Brazilian context and the other 22 (69%) associations that managed only basketball teams. Of the 32 teams, 11 (34%) of them reached a semi-final, 08 (25%) to the final and only 04 (12.5%) were champions of the competition. 60% of the titles were won by traditional multisport clubs that compete for NBB. Despite the great value that the NBB and its organizer (LNB) have regarding the resumption of the development of Brazilian basketball, LNB / NBB could undertake more with regard to the competitive balance and stimulate better management and transparency of the teams that it proposes to participate in the competition.